2011
DOI: 10.1111/j.1756-1051.2010.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Deschampsia cespitosa and soil acidification: general and trait‐specific responses to acid and aluminium stress in a solution experiment

Abstract: Genetically based adaptation and phenotypic plasticity represent important means of coping with natural or human‐induced increases in soil acidity. In the present study, we examined the role of phenotypic plasticity in the grass Deschampsia cespitosa by testing for general and trait‐specific responses to acid and aluminium (Al) stress. We sampled tussocks (genets) from sites in southern Sweden differing in their exposure to acid deposition, and quantified the performance of each genet under low pH and high Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…One possible explanation for this insensitivity might be that deep-rooted species were much more resistant to changing soil environment than the shallow-rooted species (such as sedge C. duriuscula) (Zhang et al, 2019). We found both species invested more in enhancing SRL under soil acidification, which was in agreement with Göransson et al (2011) that grass species increased root length to avoid acid stress. These results indicated that variation of root morphological traits has the potential to mitigate the negative effects of soil acidity and should be considered as part of stress-avoidance or tolerance strategies (Thomaes et al, 2013).…”
Section: Chinensissupporting
confidence: 87%
“…One possible explanation for this insensitivity might be that deep-rooted species were much more resistant to changing soil environment than the shallow-rooted species (such as sedge C. duriuscula) (Zhang et al, 2019). We found both species invested more in enhancing SRL under soil acidification, which was in agreement with Göransson et al (2011) that grass species increased root length to avoid acid stress. These results indicated that variation of root morphological traits has the potential to mitigate the negative effects of soil acidity and should be considered as part of stress-avoidance or tolerance strategies (Thomaes et al, 2013).…”
Section: Chinensissupporting
confidence: 87%
“…Weak local adaptation was found in experiments that focused on abiotic conditions connected with pH such as elevated aluminum or carbonate concentration, rather than on the effect of pH itself (Göransson et al 2009; Terés et al 2019). On the other hand, studies that focused solely on pH did not find any genetically underpinned adaptation, which suggests that phenotypic plasticity may be the most important mechanism for how plants cope with pH differences (Göransson et al 2011; Fazlioglu et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Basic soils often host different sets of species than acidic soils (Lee 1999; Hawkesford et al 2012), and populations of species that grow on both basic and acidic substrate may be adapted to the population‐specific pH. So far, there is not much known about plant adaptation to soil pH and the results of the existing studies are not conclusive (Göransson et al 2009; Göransson et al 2011; Fazlioglu et al 2017; Young et al 2018). In this study, we focused on population adaptation to soil pH across five common species of temperate grasslands in a reciprocal transplant experiment in a common garden environment.…”
Section: Introductionmentioning
confidence: 99%